AquaCrop Model Validation for Simulation Wheat Productivity under Water Stress Condition. Issue 3 (4th February 2022) - Abdou, S.M.M.; Engel, B.A.; Emam, S.M.; El-Latif, Kh. M. Abd
ABSTRACT: In Egypt, wheat is one of the most consumed cereal crops. Egypt is classified in the 12th position for wheat productivity countries globally. Two field experiments were implemented at Dar El-Ramad farm, Faculty of Agriculture, Fayoum University, Egypt, during the 2015/2016 and 2016/2017 seasons. The trials investigated the effects of ridge width for planting in wide ridges 120 cm (beds) and 60 cm ridges, flat planting (basins), and three irrigation scheduling regimes based on cumulative pan evaporation, i.e. 1.0, 0.8, and 0.6 coefficients of CPE, on wheat yield (Giza 168) and its components and some crop–water relations. The purpose of this research is to explore the validation of the AquaCrop model (version 6.1) to simulate grain wheat, biological yield, and their water productivity under suggested treatments. Statistical indicators ( R 2, RMSE, NRMSE, NSE, and D) were 0.96, 97.3, 1.58, 0.94, and 0.98 in the first season, respectively, and followed a similar trend in the second season. Similarly, the values of R 2, RMSE, NRMSE, NSE, and D for grain water productivity were 0.98, 0.02, 1.39, 0.98, and 0.99 in the 2015/16 season, respectively, and in the 2016/17 season were 0.99, 0.03, 2.00, 0.99, and 0.99, respectively.